PELATIHAN LITERASI DIGITAL UNTUK MENINGKATKAN KINERJA PELAYANAN APARATUR DESA OPAASI TAHUN 2023 - Lestari, Dian Trianita; Saputri, Shinta Arjunita; Arief, Iriyani Astuti; Sultrayansa, Sultrayansa; Tunda, Amin (Universitas Halu Oleo, 2023)
The Internal Community Service Program, titled Digital Literacy Training to Improve the Service Performance of Opaasi Village Officials in 2023, aims to increase Opaasi village officials' digital literacy understanding in order to create a digital-based government system. As a result, the service team provided training in the form of an introduction to the substance of a digital-based government system, as well as a Village Seminar on the importance of digital literacy and media on how to avoid fake news. This is done because the object of service still has limited awareness of digital literacy. Furthermore, as time passes, the quality of service to village communities must become easier and more effective. The service team uses media such as websites and power point presentations to communicate knowledge and ideals to village leaders through this training method. The team engages with partners in this service activity, notably Opaasi Village Government Officials. The outcomes of this service will be critical in preparing Opaasi community to become a digital community by 2024. The service team created a website, social media profiles, and e-mail to help the Opaasi village government communicate its policies to the community.